Transport, Telecommunications, Environment and Energy - Gjini, Anjeza; Sefa, Stela (Mediterranean Journal of Social Sciences, 2012)
The presented study takes in consideration the environmental impacts of transportation, transportation and energy,transportation and alternative fuels, including the impact of the transportation in the Albanian Economy.The transportation sector islinked to environmental problems, because the transport activities have resulted in growing levels of motorization and congestion. Andalso transportation activities support increasing mobility demands for passengers and freight. This is ranging from urban areas tointernational trade. Environmental impact of transportation can fall within three categories: direct impacts, indirect impacts, cumulativeimpacts. The environmental impacts of transportation is relate to air quality, water quality, climate change, noise, biodiversity. Energyand the activities of transport are closely related to each other. Energy consumption has strong modal variations: land transportation,maritime transportation, air transportation. Fossil energy reserves are exhaustible. In this study are set out possible solutions toeliminate the negative effects of transport on the environment in Albania.